Regional modeling of tropospheric delay considering vertically and horizontally separation of station for regional augmented PPP. Issue 10 (15th November 2020) - Li, Yangyang; Zou, Xuan; Tang, Weiming; Deng, Chenlong; Cui, Jianhui; Wang, Yawei
Abstract: Considering the height and horizontal separations between stations, we propose a method to regionally model the tropospheric delay. The zenith tropospheric delay (ZTD) is separated into vertically-correlated and horizontally-correlated components, which are to be regionally modeled respectively. A more accurate ZTD is thereby interpolated at the rover station, and enhanced ZTD constraints can be provided for precise point positioning (PPP). A new constraint of the ZTD interpolation error is proposed and assessed. The results show that the linear correlation between ZTD after separation and the height of the station are further enhanced, with the mean correlation coefficient reaching up to 0.99. The RMS value of the ZTD obtained from undifferenced and uncombined PPP with fixed station coordinates is less than 6.5 mm. The new method is compared with conventional modeling methods and the results show that the new zenith tropospheric delay modeling method is superior to other methods, yielding a RMS value within 1 cm. Simulated kinematic positioning experiments for five different elevation cutoff angles from 10° to 50° are performed to evaluate the performance of the new method. Experimental results show that the new method can effectively improve the convergence and positioning accuracy. The systematic deviations of the vertical component for the higher cutoff angle solution can be significantly improved by the new method.